O Movimento Escoteiro em Bragança - Pará, como ambiente de educação não formal - BRANDÃO, José Rick Moreira (2021)
This work focuses on the Scout Movement and non-Formal education, specifically on the Scout Groups Sebastião Pereira 85/PA and Jorge Ramos 45/PA, both located in the city of Bragança-to, Brazil. The general objective consisted of analyzing the educational practices developed in the Scout groups of the city, with a view to identifying them as spaces of non-formal education. This is a qualitative research, with methodological techniques such as bibliographical studies, semi-structured interviews and documentary analysis. The results of the survey indicate that the Scout movement in Bragança-PA, represents an expressive environment with regard to practices of non-formal education, which can converge to the formation of critical and participative citizens.